Analisis Keuntungan Usahatani Selada Hidroponik Umaniniafarm Di Kelurahan Wailan Kecamatan Tomohon Utara Kota Tomohon - Tarigan, Helena; Laoh, Esry Olly Harryani; Jocom, Sherly Gladys (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2024)
The purpose of this study was to analyze the profitability of Umaninia Farm's hydroponic lettuce farming. Umaninia Farm in Wailan Village, North Tomohon District, Tomohon City. Tomohon. This research was carried out for four months, starting from April to July 2024 from proposal preparation to undergraduate examination in Wailan Village, North Tomohon District, Tomohon City. Data analysis data analysis used in this research is Quantitative analysis. Data collection method data using observation, interview and documentation techniques. Research results The results showed that the acceptance of Umaninia Farm hydroponic lettuce farming was amounted to Rp.12,750,000 while the costs incurred in hydroponic lettuce farming for 45 days amounted to Rp.12,750,000. hydroponic lettuce farming for 45 days amounted to Rp. 4,567,321.57 So that the profit earned in hydroponic lettuce farming is Rp. 12,750,000. in hydroponic lettuce farming UmaniniaFarm amounted to Rp.8,182,678.43 with a planting period of 45 days using 2,500 plants. 45-day planting period using 2,500 nettpot.